The Cause Of Corruption Crime On Village Funds And Investigations Process In The Purworejo - Bruyi Rohman Warsito; Ira Alia Maerani (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Corruption has caused damage in various aspects of community life, the nation and the state, so it must be eradicated in order to realize a just and prosperous society based on Pancasila and the Constitution of 1945. Since 2015-2017 in Purworejo have been many complaints from the public about Corruption allegations of village funds, so the authors are interested in writing causes of corruption and the village funds investigation in Purworejo, source used in the study of primary data and secondary data, engineering data collection was done by interview. The results of research into the causes of corruption lack / role of the community in the planning and supervision of village funds, the limited competence and ability of the village head and village, the three are not optimal role of village institutions. For the process of Police investigation in Purworejo create a unit specifically dealing with corruption. As for the constraints of investigation number of witnesses testified that most of the people close to the village head so much that did not cooperate and testify often convoluted, besides documents relating Village funds also difficult to establish the suspect must await the results of the calculation of damages State Auditors do that requires a long time so impressed Investigation tele on Village funds.Keywords: Crime of Corruption; Village Funds; Investigation Process.